2018
DOI: 10.1002/2017wr021488
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Experiments in Microbially Induced Calcite Precipitation (MICP): Reactive Transport Model Development and Prediction

Abstract: Design of in situ microbially induced calcite precipitation (MICP) strategies relies on a predictive capability. To date much of the mathematical modeling of MICP has focused on small‐scale experiments and/or one‐dimensional flow in porous media, and successful parameterizations of models in these settings may not pertain to larger scales or to nonuniform, transient flows. Our objective in this article is to report on modeling to test our ability to predict behavior of MICP under controlled conditions in a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…In both specimens, C/C o values consistently increased more rapidly with injected volume along W1 to W2. Breakthrough curves from W2 to W3 were consistent with measured soil porosities and expected trends from numerical models 39 , suggesting that the W1 to W2 alignment may have been initially partially-saturated. Despite these differences, similar breakthrough curves for each well alignment suggested that advective-dispersive solution transport between tanks was comparable prior to treatments.
Figure 2Normalized bromide concentrations (C/Co) versus injected pore volumes (PV) from passive tracer testing completed from ( a ) Well 1 to Well 2 and ( b ) Well 2 to Well 3.
…”
Section: Resultssupporting
confidence: 77%
“…In both specimens, C/C o values consistently increased more rapidly with injected volume along W1 to W2. Breakthrough curves from W2 to W3 were consistent with measured soil porosities and expected trends from numerical models 39 , suggesting that the W1 to W2 alignment may have been initially partially-saturated. Despite these differences, similar breakthrough curves for each well alignment suggested that advective-dispersive solution transport between tanks was comparable prior to treatments.
Figure 2Normalized bromide concentrations (C/Co) versus injected pore volumes (PV) from passive tracer testing completed from ( a ) Well 1 to Well 2 and ( b ) Well 2 to Well 3.
…”
Section: Resultssupporting
confidence: 77%
“…What we consider important for investigating the upscaling of MICP processes between the laboratory and the field scale is a close cooperation between experimentalists and modelers, as demonstrated in this study and others, e.g., by [51], and, very importantly, more well-controlled largerscale experiments such as those conducted by [56]. A second, equally important, issue is that information on the setup is drastically reduced compared to well-controlled laboratory work, thus complicating determination of correct initial and boundary conditions or other properties of the simulation setup such as the initial distribution of porosity and permeability.…”
Section: The State Of the Micp Model So Farsupporting
confidence: 54%
“…Applications found in the literature include the interaction of microbes with the subsurface transport of contaminants, [e.g., 37,63,69,74], microbially enhanced oil recovery [e.g., 44,53,54,72], or biomineralization, of which especially the engineered application of MICP has received considerable attention. Most numerical models for MICP are, similarly to the model used in this study, formulated at the REV scale (or Darcy scale) [e.g., 2,17,46,51,[76][77][78], while [64] and [80][81][82] use pore-network and pore-scale models, respectively.…”
Section: Model Developmentmentioning
confidence: 99%
“…Even then, just growing and preserving the involved microorganisms under fieldlevel conditions would have its own set of complications. After two decades of active MICP research, therefore, it is noteworthy that relatively few large, meter-scale projects have yet been attempted within either lab or field studies using sand and natural soil systems (Burbank et al 2011;Gomez et al 2015;De Jong et al 2009;Nassar et al 2018;van Paassen et al 2009van Paassen et al , 2010a van Paassen 2011; Phillips et al 2016;van der Star et al 2011).…”
mentioning
confidence: 99%